Next-Generation Composite Coating System: Nanocoating - Bao, Weiwei; Deng, Zhifeng; Zhang, Shaodan; Ji, Zhuoting; Zhang, Haichang (Frontiers in Materials, 2019)
Nanocoating combine the protective properties of conventional coating system with effects on nanoscale such as high hardness, UV scattering, uniform dispersing, etc. Their facile and low-cost synthesis, together with superior protective properties and multi-functionalities, makes nanocoating attractive candidates for next-generation coating system. In this review, a brief introduction regarding to mainstream nanocoating and its related challenges including the zinc oxide-, titanium dioxide-, silica dioxide-, graphene-, carbon nanotube-based nanocoating system is presented. Finally, a perspective of the nanocoating is demonstrated.